2022
DOI: 10.17159/caj/2022/32/2.14588
|View full text |Cite
|
Sign up to set email alerts
|

Temperature modifies the association between air pollution and respiratory disease hospital admissions in an industrial area of South Africa: The Vaal Triangle Air Pollution Priority Area

Abstract: Background: Epidemiological studies reported independent effects of air pollution and temperature on health, yet these twoexposures are often treated as separate risk factors. Few studies investigated temperature effect modification on the health effects ofair pollution in Africa and none examined the effects of black carbon on respiratory disease (RD) hospitalisations. The aim of this studywas to determine whether the association between RD hospitalisations and air pollution in the Vaal Triangle Air Pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Although there are air quality regulations to manage the criteria for air pollutants in South Africa, air pollution continues to be a public health concern. Recent studies conducted in South Africa have reported air pollution levels (e.g., PM 2.5 ) that have exceeded the WHO air quality guidelines and the South African National Quality Standards [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are air quality regulations to manage the criteria for air pollutants in South Africa, air pollution continues to be a public health concern. Recent studies conducted in South Africa have reported air pollution levels (e.g., PM 2.5 ) that have exceeded the WHO air quality guidelines and the South African National Quality Standards [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%